Impacts of Meaning and Measurement of Risk-on-Risk Disclosure: An Empirical Study - Ali Alagöz; Omed Mohammed Mamand (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
The literature on risk has focused on different issues, such as the quantity and quality aspects of risk, how efficiently it is reported, and its role in increasing transparency. The current study aims to investigate the impact of risk meaning and risk measurement (assessment) on risk disclosure. In light of the empirical findings, this research study provides an in-depth understanding of the relationship between risk meaning and measurement and risk disclosure. This study considers the perceptions of the stakeholders; investors, shareholders (owners), management, and external auditors, because they are either users of risk disclosure or preparers of this kind of information. The data for the study were gathered using a questionnaire, which was distributed to key stakeholders. The study revealed a positive relationship between the meaning of risk and risk disclosure on the one hand and a positive association between the measurement of risk and risk disclosure on the other. This study extended the literature by providing empirical evidence that disclosure of risk can be affected by the meaning and measurement of risk on one side. Furthermore, Provide information about business environments such as those in Sulaimaniyah, Iraq.